2001
DOI: 10.1126/science.1066333
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Arp2/3 Complex

Abstract: We determined a crystal structure of bovine Arp2/3 complex, an assembly of seven proteins that initiates actin polymerization in eukaryotic cells, at 2.0 angstrom resolution. Actin-related protein 2 (Arp2) and Arp3 are folded like actin, with distinctive surface features. Subunits ARPC2 p34 and ARPC4 p20 in the core of the complex associate through long carboxyl-terminal alpha helices and have similarly folded amino-terminal alpha/beta domains. ARPC1 p40 is a seven-blade beta propeller with an insertion that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
592
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 489 publications
(623 citation statements)
references
References 37 publications
25
592
1
5
Order By: Relevance
“…These features also had the highest B-factors or were disordered in crystal structures. 19,21,30 When ATP was added to nucleotide-free Arp3, the cleft did not close, as observed in Arp2/3 complex crystal structures, but opened in a fashion similar to the other Arp3 simulations.…”
Section: Overview Of Simulationsmentioning
confidence: 90%
See 3 more Smart Citations
“…These features also had the highest B-factors or were disordered in crystal structures. 19,21,30 When ATP was added to nucleotide-free Arp3, the cleft did not close, as observed in Arp2/3 complex crystal structures, but opened in a fashion similar to the other Arp3 simulations.…”
Section: Overview Of Simulationsmentioning
confidence: 90%
“…First, among the nine currently available crystal structures of the Arp2/3 complex, the 5 C-terminal residues of Arp3 that extend beyond the C-terminus of actin show a greater tendency to be ordered when the nucleotide cleft of Arp3 is open than when it is closed. [19][20][21] In the three Arp3 structures with open nucleotide binding clefts, an average of 3.4 of these 5 residues is ordered, while in the three structures with closed clefts, an average of 0.3 of these 5 residues is ordered. This difference suggests that stable interactions of the C-terminal extension with the groove between subdomains 1 and 3 facilitate closure of the barbed-end groove and promote the rigid body motion that opens the nucleotide binding cleft.…”
Section: Structural Basis For Differences Between Actin and Arp3mentioning
confidence: 99%
See 2 more Smart Citations
“…Intensive studies had revealed that VCA's ability to bind monomer actin through its V subdomain is critical for actin nucleation (Miki and Takenawa, 1998). The CA subdomain confers to N-WASP its binding ability to the Arp2/3 complex as evidenced by physicochemical assays (Machesky and Insall, 1998;Marchand et al, 2001) and x-ray crystallography and cross-linking experiments (Gournier et al, 2001;Robinson et al, 2001;Zalevsky et al, 2001). Actin polymerization, nucleation, and branching are enhanced in the presence of VCA protein in vitro Machesky et al, 1999;Rohatgi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%